Postgrowth Imaginaries. New Ecologies and Counterhegemonic Culture in post-2008 Spain. Luis I. Prádanos. Liverpool: Liverpool University Press, 2018 - Vico, Eva Aladro (CIC. Cuadernos de Información y Comunicación, 2020)
Reseña del libro de Luis I. Prádanos, Postgrowth Imaginaries. New Ecologies and Counterhegemonic Culture in post-2008 Spain. . Liverpool: Liverpool University Press, 2018